The role of molecular biomarkers in outcomes and patient selection for cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for peritoneal metastases of colorectal origin. Issue 6 (December 2021) - Solomon, Daniel; Leigh, Natasha; Bekhor, Eliahu; Feferman, Yael; Dhorajiya, Poojaben; Feingold, Daniela; Hofstedt, Margaret; Aycart, Samantha N.; Golas, Benjamin J.; Sarpel, Umut; Labow, Daniel M.; Magge, Deepa R.
Abstract: Background: Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) is effective in select patients with peritoneal metastases of colorectal (CRC) origin. The impact of different biomarkers in predicting recurrence after CRS/HIPEC is unclear. Methods: Retrospective review of patients who underwent CRS/HIPEC for PC of CRC origin from 03/2007–08/2017. Molecular profile of the primary tumor was obtained from pathology reports, whenever available. Results: Overall, 100 patients underwent CRS/HIPEC for peritoneal metastases of CRC origin. Most patients presented high grade tumor histology (G2/G3, n = 97, 97%), and a majority showed mucinous features (n = 61, 61%). At a median follow-up of 18 months, median DFS for the overall population was 13 months (95% CI 9.6, 16.4). Data reporting at least one mutational analysis was available in 64 patients. Microsatellite stability was detected in 42/50 (84%) patients, mKRAS in 25/51 (49%), and mBRAF in 5/35 (14.3%). On Kaplan–Meier analysis, BRAF was the only mutation associated with poor DFS (16 months, CI 95% 11.7–43.3 vs. 7 months, CI 95% 2.1–11.9, p = .008). On multivariate analysis, mBRAF independently predicted earlier recurrence (p = .032). Conclusions: In this analysis, mBRAF was independently associated with earlier recurrence in patients undergoing CRS/HIPEC for CRC, leading to dismal median DFS (7 months). Strict patient selection is advisable in these patients. Highlights: - Role of biomarkers in predicting outcomes after CRS/HIPEC for CRC is unclear - High rates of mKRAS were identified among CRC patients - mBRAF status was associated with poor OS and DFS - mBRAF was independently associated with earlier recurrence